Multiple liver masses mimicking metastatic liver disease in an elderly patient - Hayretdin Köklü,; Berkan Armağan,; Ömer Karadağ,; Musturay Karcaaltıncaba,; Müzeyyen Pınar Özgen Kıratlı,; Gökhan Gedikoğlu,; Taylan Kav, (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Köklü H, Armağan B, Karadağ Ö, et al. Multiple liver masses mimicking metastatic liver disease in an elderly patient. Turk J Gastroenterol 2018; 29: 115-8.